Cell-Extrinsic Priming Increases Permissiveness of CD4+ T Cells to Human Immunodeficiency Virus Infection by Increasing C–C Chemokine Receptor Type 5 Co-receptor Expression and Cellular Activation Status - Pedersen, Jesper G.; Egedal, Johanne H.; Packard, Thomas A.; Thavachelvam, Karthiga; Xie, Guorui; van der Sluis, Renée Marije; Greene, Warner C.; Roan, Nadia R.; Jakobsen, Martin R. (Frontiers in Microbiology, 2021)
The chemokine receptor CCR5 is expressed on multiple cell types, including macrophages, dendritic cells, and T cells, and is the major co-receptor used during HIV transmission. Using a standard αCD3/CD28 in vitro stimulation protocol to render CD4+ T cells from PBMCs permissive to HIV infection, we discovered that the percentage of CCR5+ T cells was significantly elevated in CD4+ T cells when stimulated in the presence of PBMCs as compared to when stimulated as purified CD4+ T cells. This indicated that environmental factors unique to the T-PBMCs condition affect surface expression of CCR5 on CD4+ T cells. Conditioned media from αCD3/CD28-stimulated PBMCs induced CCR5 expression in cultures of unstimulated cells. Cytokine profile analysis of these media suggests IL-12 as an inducer of CCR5 expression. Mass cytometric analysis showed that stimulated T-PBMCs exhibited a uniquely activated phenotype compared to T-Pure. In line with increased CCR5 expression and activation status in stimulated T-PBMCs, CD4+ T cells from these cultures were more susceptible to infection by CCR5-tropic HIV-1 as compared with T-Pure cells. These results suggest that in order to increase ex vivo infection rates of blood-derived CD4+ T cells, standard stimulation protocols used in HIV infection studies should implement T-PBMCs or purified CD4+ T cells should be supplemented with IL-12.